Wage differentials within a female dominated occupation: domestic workers in informal and flexible jobs in Portugal - Suleman, F.; Figueiredo, M. C. (International Labour Review, 2018)
We use an original dataset to examine the impact of informal and flexible contractual arrangements on wages of a sample of domestic workers hired by private employers in Portugal. All arrangements should be formal involving declaration of employment relationship to social security authorities. Our results suggest formality benefits workers whether they have stable or flexible contract. However, social and labour market processes help shape and maintain inequality, especially for migrant workers. Specific and general skills are undervalued and are unable to generate rewards. Compensation was identified for contingent work, multiple employers and elderly caregivers but this hides exploitation and insecurity.